Dynamic Pricing with Stochastic Entry - Deshmukh, S. D.; Chikte, S. D. (Review of Economic Studies, 1976)
S. D. Deshmukh, S. D. Chikte; Dynamic Pricing with Stochastic Entry, The Review of Economic Studies, Volume 43, Issue 1, 1 February 1976, Pages 91–97, https://d